Fabrication of Bi2S3/ZnO heterostructures: an excellent photocatalyst for visible-light-driven hydrogen generation and photoelectrochemical properties. (6th December 2017) - Bera, Susmita; Ghosh, Srabanti; Basu, Rajendra N.
Abstract : Bi2 S3 /ZnO heterostructures were synthesized, showing a high catalytic effect in photocatalytic hydrogen generation and organic dye degradation under visible light. Abstract : Fabrication of heterostructures is considered as one of the effective strategies to improve photocatalytic performance for organic pollutant degradation and hydrogen production under solar light irradiation. Here, Bi2 S3 /ZnO heterostructures with a flower-like architecture have been successfully synthesized by a facile in situ generation method. The as-synthesized Bi2 S3 /ZnO heterostructures showed enhanced visible-light absorption and charge separation efficiency of photoinduced electron–hole pairs. This heterojunction exhibits 3 fold enhancement in organic pollutant degradation and 2.7 fold enhancement in photocatalytic hydrogen generation under visible irradiation compared to rod-shaped Bi2 S3 . The high current gain ( ca. 8.79) and low photocorrosion in photoelectrochemical water splitting reveal the superior photocatalytic activity of the heterojunction under visible light. The superior photocatalytic activities are attributed to the synergetic effects of ZnO nanoparticles and rod-shaped Bi2 S3 in the Bi2 S3 /ZnO heterostructures, which result in fast separation and slow recombination of photoinduced electron–hole pairs. The reusability and stability of the photocatalysts has been checked by recycling experiments. X-ray diffraction and scanning electron microscopy reveal that the structure and morphology of the heterostructures remain unchanged after photocatalytic cycling tests. The visible light active catalysts have potential for efficient solar light harvesting and overall water splitting. This work demonstrates the potential use of heterostructures as a highly efficient photocatalyst for dye degradation and hydrogen production under visible light irradiation.